Write y grow rich: using speech recognition to dictate your how-to book - Poynter, Dan (Santa Bárbara: Library of congress catalogueing, 1999)
Contents: 1. what your book will do for you. 2. what to write selecting your subject. 3. researching your topic and checking for competition. 4. your book's title and subtitle. 5. your book's covers. 6. getting organized setting up your binder. 7. your writing system. 8. If you can speak it, you just wrote it. 9. your publishing choices. selling to a publisher or publishing yourself. 10. finding a publisher finding an agent.
Keywords: Authorship - Automatic Speech Recognition